Genetic studies on water buffalo species (Bubalus bubalis) in Cuba - García, Yenny; Fraga, Luis M.; Padrón, Eulogio; Rodríguez, Norma; Alcides, Amorim [UNESP]; Guzmán, Gladys; Mora, Marta (My University, 2010)
In order to increase performance qualities in the Bubalus bubalis species in Cuba it has been developped a National Buffalo Breeding Program. This study was conducted at the Genetic Enterprise El Cangre, advanced representation of our bubalino culture with the objetive to characterize their productive and reproductive performances, to select cow buffaloes based on milking production and to evaluate albinoidism frequency. It was employed the GLM proc of SAS 2007 and the Statgraphics software to analyse data utilizing a linear model of fixed effect considering: herd, calving year, calving season (on season: August-October/out of season: November-July) and calf progeny sex. General means were: Total milk, Lactation length, Milk/lactation days, calving interval, open days and dry period. Cow buffaloes were classificated according total milk production during lactation. Gene frequencies corresponding to different coat color genotypes were contrasted with those expected from a population in equilibrium Hardy-Weinberg. It was observed that productive and reproductive traits were acceptable in relation to those nationally reported. It was also demonstrated that herd, calving year and season affected the different traits occurring the greatest calving frequency between August and October influencing milking production and dry period. A wide rank was presented on individual cow milk production classification that must be taken into account to female selection. Albinoidism was pressented as corresponding to a single recesive gen that in homozygous state express the albinoide fenotype and at the heterozygous to blondy individuals.
Keywords: Albinoidism; Búfalo; Productive-reproductive